2022
DOI: 10.3390/biology11060890
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and Nutrients-Induced Phenotypic Changes of Antarctic Green Snow Bacteria Probed by High-Throughput FTIR Spectroscopy

Abstract: Temperature fluctuations and nutrient composition are the main parameters influencing green snow microbiome. In this study we investigated the influence of temperature and nutrient conditions on the growth and cellular chemical profile of bacteria isolated from green snow. Chemical profiling of the green snow bacteria was done by high-throughput FTIR spectroscopy combined with multivariate data analysis. We showed that temperature and nutrients fluctuations strongly affect growth ability and chemical profile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 91 publications
2
11
0
Order By: Relevance
“…Strain Leifsonia antarctica BIM B-1671 showed a fatty acid profile distinctly different from all other Leifsonia strains (Figure S3-S5 in the Supporting Information). This and other previously reported considerable similarities of the total cellular biochemical profile of this strain with Pseudomonas (Smirnova et al, 2021;Smirnova et al, 2022) can be an indication of misidentification by 16S rRNA gene sequencing.…”
Section: Notesupporting
confidence: 75%
See 1 more Smart Citation
“…Strain Leifsonia antarctica BIM B-1671 showed a fatty acid profile distinctly different from all other Leifsonia strains (Figure S3-S5 in the Supporting Information). This and other previously reported considerable similarities of the total cellular biochemical profile of this strain with Pseudomonas (Smirnova et al, 2021;Smirnova et al, 2022) can be an indication of misidentification by 16S rRNA gene sequencing.…”
Section: Notesupporting
confidence: 75%
“…It can be seen that growth ability at different temperatures was more genus and species-specific. For example, Actinobacteria from the genus Salinibacterium were not able to grow in liquid culture at 5 C and 25 C but grew well on agar media (Smirnova et al, 2022). Strains from the genus Salinibacterium and some species, such as Leifsonia rubra and Facklamia tabacinasalis, exhibited heightened susceptibility to both high (25 C) and low (5 C) temperatures, with better growth occurring exclusively at 15 C. Strains within genera Polaromonas, Psychrobacter, Flavobacterium, Carnobacterium, Rhodococcus, Salinibacterium and Paeniglutamicibacter were identified as psychrophiles (did not grow at 25 C), according to their growth in broth media.…”
Section: Resultsmentioning
confidence: 99%
“…R5-57. This combined with results from other studies using FTIR suggest that differences in morphology and chemical composition of bacteria and bacterial polymers means any attempt to make quantitative models for PHA should be species-or strain-and instrument specific [53][54][55].…”
Section: Plos Onementioning
confidence: 78%
“…Due to the fact that the isolation of bacteria was conducted for two weeks and all selected isolates retrieved within this time were able to produce single colonies within 2–6 days, we concluded that these isolated bacteria could be considered to be fast-growing [ 14 , 46 , 47 ]. In total, twenty-nine fast-growing bacteria with different colony types (colony morphology, size, and pigmentation) and growth rates were isolated from nine MPs of East Antarctica.…”
Section: Resultsmentioning
confidence: 99%